Health outcomes in people with rare autoimmune rheumatic diseases before and during the COVID-19 pandemic and the effect of corticosteroids: whole population data from England - Rutter, Megan (2023)
Introduction: Rare autoimmune rheumatic diseases (RAIRD) are a heterogenous group of immune-mediated inflammatory diseases. They are chronic and often require immunosuppression.